Protective effect of Lactobacillus delbrueckii subsp. Lactis CIDCA 133 in a model of 5 Fluorouracil-Induced intestinal mucositis - De Jesus, Luís Cláudio Lima (2019)
Mucositis is a cytotoxic side effect caused by chemotherapy drugs, such as 5-Fluorouracil (5-FU), being a serious clinical issue. Lactobacillus spp. could be a helpful strategy to alleviate 5-FU chemotherapy-caused intestinal damage, due to their ability to contribute to intestinal homeostasis through improvement of microbiota balance and immunomodulation. In this work we evaluated the effect of Lactobacillus delbrueckii subsp. lactis CIDCA 133 fermented milk in 5-FU-induced experimental mucositis. Intestinal histology, permeability and biochemical parameters showed that animals administrated with 5-FU and treated with CIDCA 133 fermented milk presented reduced intestinal IgA secretion and lower permeability in the small bowel. We showed that this strain preserves villus/crypt ratio, reduces the loss of goblet cells and inflammatory infiltration in ileum sections of 5-FU-treated animals. In conclusion, CIDCA 133 is able to prevent the intestinal mucosa damage caused by 5-FU revealing to be a promising strategy for intestinal mucositis treatment.